Association between Nutritional Status and Severity of Pneumonia in Under Five Years of Children Admitted at Birat Medical College Teaching Hospital - Yadav, Satish; Yadav, Ramesh; Mahat, Ramesh Kumar; Rimal, Hemsagar (Nepalese Medical Journal, 2024)
Introduction: Childhood malnutrition is common in low-income and middle-income countries and increases the frequency and severity of pneumonia. The objective of this study was to determine the association between nutritional status and severity of pneumonia in under five children.Materials and Methods: This was a hospital-based cross-sectional study of data of children between 3 months to 5 years admitted in the Department of Pediatrics of Birat Medical College Teaching Hospital with a clinical diagnosis of pneumonia from December 2023 to July 2024.Results: One hundred seventy children were included in the study with a majority of age group 3 to 12 months (46.5 %) and male to female ratio of 3:1. There were 69 (40.6%) undernourished children and 73 (42.9%) anemic. On applying bivariate analysis, undernourishment(p